COUNTRY OF ORIGIN AS ANTECEDENTS ON CONSUMER QUALITY PERCEPTIONS AND PUCHASING DECISIONS - Wijaya, Tony (Benefit: Jurnal Manajemen dan Bisnis, 2019)
This research aimed to analyze consumer purchase decisions and consumer perceptions of the quality of car products based on country of origin factors namely country of manufacture, brand, and price, country of assembling and country of design hybrid brand products. Respondents in this study amounted to 384 respondents using purposive sampling where this method is a sampling method by determining the criteria in the sample to be studied. The criteria in question are consumers who have plans to buy a car, look for car product information, have or own a car and keep up with car product development. The data analysis method used in this study is conjoint analysis. Based on the results of data analysis, country of origin factors, that is the most important for consumers to consider in purchasing car products and quality perception is a country of manufacture. Country of manufacture is trusted by consumers as a basis for consideration in evaluating especially automotive products. Consumers assess the country of manufacture will show performance in accordance with the country that is believed.